DEKONTRUKSI ASET TETAP PEMERINTAHAN (PADA AKUNTAN DI KOTA BANJARMASIN) - Monica Rahardian Ary Helmina; Ayu Oktaviani; Pusvita Indria Mei Susilowati; Ibnu Sutomo (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
The purpose of this study is to deconstruct the understanding of fixed assets in government institutions, using deconstructive semiotic studies based on Jacques Derrida's philosophy. Specifically, the research objectives are First, to understand the interpretation of financial statement providers on fixed assets, and evaluate their understanding of the concept of fixed assets applied in accounting. Second, carrying out a search for meaning (semiotics) structurally and deconstructive on the interpretation of fixed assets to reveal the structural reality that appears on the surface and is hidden behind the interpretation. This type of research is qualitative. Respondents were accountants in Banjarmasin, consisting of teaching accountants, government accountants, management accountants and public accountants. The results of the study concluded that accountants clearly understood the definition of fixed assets, especially government fixed assets. The structural meaning of semiotics Assets are all economic resources as a result of past events that have been controlled, owned by the government, assets have future economic and social benefits that will be achieved, either by the government or the community. Assets can be measured in terms of money, as well as non-financial resources. Necessary for the provision of services to the general public and these resources are maintained due to history and culture. Assets can be purchased on the APBD. Government assets that are the property of the government are obtained from past activities that are used for economic or social activities and are continuously used by the government. Assets can be measured in units of money, non-financial useful life of more than 12 months. Intended for use, in government or public activities. This finding has a fundamental contribution to the field of accounting science because it provides semiotic fundamental ideas for accounting standard setting policies